The birthday ball - Lowry, Lois (Houghton Mifflin Books for Children, 2010)
When a bored Princess Patricia Priscilla makes her chambermaid switch identities with her so she can attend the village school, her attitude changes and she plans a new way to celebrate her sixteenth birthday.